The world Jones made - Dick, Philip K. (London : Gollancz, 2010)
Floyd Jones, a sullen, ungainly fortune teller who has the ability to see one year into the future, builds a mass movement in opposition to the government and its philosophy of relativism.
"Originally published in paperback by Ace Book, New York, in 1956"--T.p. verso.
Adult.
Adult
Keywords: Dreams -- Fiction; Psychics -- Fiction; Dreams -- Fiction; Psychics -- Fiction; Science fiction; Science fiction